2014
DOI: 10.1007/s13762-014-0653-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced fluoride removal by hydroxyapatite-modified activated alumina

Abstract: Fluoride in drinking water is beneficial at low concentrations but is considered harmful for the human health when present at concentrations exceeding 1.5 mg/L. Prevalence of high concentration of fluoride in drinking water, combined with the nonavailability of alternate viable sources, makes the treatment of the contaminated water an essential task. In this study, we report the synthesis and characterization of a hybrid adsorbent; hydroxyapatitemodified activated alumina (HMAA) prepared by dispersing nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…From the FT-IR spectrum of HAP, peak values at 1,034 and 1,107 cm À1 are characteristic peaks of symmetric stretching vibrations of the phosphate group, and peaks at 563 and 603 cm À1 are attributed to bending vibrations of the phosphate group (Wang et al 2011). In the spectrum of Al-HAP, the absorption peaks at 3,443 and 1,646 cm À1 belong to hydroxyl stretching vibrations, where the peak at 1,646 cm À1 , which is likely attributed to Al-OH-A, exhibits a blue shift and a significant increase in intensity, indicating that Al modification has increased the number of -OH groups in the material (Gogoi et al 2015;Tomar et al 2015). At the same time, the phosphate group peaks after Al modification show slight variations, possibly due to changes in the bending vibrations of the P•••O bond caused by the Al•••P bond (Bouiahya et al 2019), indicating that the Al-HAP material modified by aluminum ions does not change the position and structure of functional groups but simply increases the -OH content, and its main structure remains that of hydroxyapatite.…”
Section: Sem and Eds And Ft-ir Analysismentioning
confidence: 99%
“…From the FT-IR spectrum of HAP, peak values at 1,034 and 1,107 cm À1 are characteristic peaks of symmetric stretching vibrations of the phosphate group, and peaks at 563 and 603 cm À1 are attributed to bending vibrations of the phosphate group (Wang et al 2011). In the spectrum of Al-HAP, the absorption peaks at 3,443 and 1,646 cm À1 belong to hydroxyl stretching vibrations, where the peak at 1,646 cm À1 , which is likely attributed to Al-OH-A, exhibits a blue shift and a significant increase in intensity, indicating that Al modification has increased the number of -OH groups in the material (Gogoi et al 2015;Tomar et al 2015). At the same time, the phosphate group peaks after Al modification show slight variations, possibly due to changes in the bending vibrations of the P•••O bond caused by the Al•••P bond (Bouiahya et al 2019), indicating that the Al-HAP material modified by aluminum ions does not change the position and structure of functional groups but simply increases the -OH content, and its main structure remains that of hydroxyapatite.…”
Section: Sem and Eds And Ft-ir Analysismentioning
confidence: 99%
“…Fluoride is one of the major pollutants naturally from the soil, which causes adverse effects on human health if there is longterm consumption of water with its concentration above WHO recommended value (0.5-1.5 mg l −1 ). Dental and skeletal fluorosis is one of the most apparent health risks common in different countries (Tomar et al 2015, Demelash et al 2019, Fernando et al 2019. Therefore, defluoridation using the various techniques such as precipitation, ion exchange, adsorption, membrane and electrochemical methods is in progress (He et al 2020, Alhassan et al 2021, Huang et al 2022.The adsorption process is more attractive to researchers than other techniques in terms of cost, efficiency, flexibility, simple and ease of operation (Yang et al 2019(Yang et al , Özsin et al 2019a.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, adsorption is extensively used due to its reusability and simplicity. 19 Activated carbon, 20 activated alumina, 21 LDHs, 22 and MOFs 23 have been reported for the adsorption of F − . Yang et al 24 reported an amorphous porous Al 2 O 3 microfiber cluster to adsorb F − , and its adsorption capacity was 10.8 mg g −1 .…”
Section: ■ Introductionmentioning
confidence: 99%